Surgical complications of cochlear implantation: a 25-year retrospective analysis of cases in a tertiary academic center - BİNNETOĞLU, ADEM; BATMAN, ABDULLAH ÇAĞLAR (SPRINGER, 2020)
Purpose Despite the advances made in cochlear implantation techniques, the associated complication rates are still high. Here, we aimed to analyze cases, with extensive follow-up data, associated with a large sample of patients to identify complications related to cochlear implants and to present our surgical experience and the technique that we used in order to follow surgical rules/medical purpose to avoid any complications. Methods We retrospectively examined cases involving 2597 patients (1342 males; 1255 females; age 1-88 years) who underwent cochlear implantation procedures between November 1995 and July 2019, and we classified complications as minor and major. Results The mean age at the time of implantation was 6.48 (Min: 1/Max: 88) years. The cause of deafness was congenital in 76.5% of the patients and acquired in 16.8%. The overall rate of complications in the study was 3.7% (n = 97). The minor and major complication rates were 3.0 and 0.7, respectively. Further, while the most common minor complication we encountered was vertigo, the most common major complication was implant extrusion. Conclusion Fixing the cochlear implant receiver-stimulator with the bone-recess technique and sealing the posterior tympanotomy site with a piece of muscle in order to follow surgical rules/medical purpose to avoid any complications. Following the insertion of the electrode into the cochlea, the muscle closure of the cochleostomy site or the round window restores the original anatomy and in order to follow surgical rules/medical purpose to avoid any complications. We have developed this highly effective technique with years of experience and have not had a major surgical complication in 5 years.
Keywords: Cochlear implant; Postoperative complications; Implant extrusion; Complication prevention; Sensorineural hearing loss; Congenital hearing loss; VESTIBULAR FUNCTION